Repair of isolated double-chambered right ventricle - M El Kouache; A Babakhoya; S Labib; A El Madi; S Atmani; M Harandou; Y Abouabdilah; M Hida (Wolters Kluwer Medknow Publications, 2013)
The finding of a double-chambered right ventricle (DCRV) is exceptionally rare as an isolated anomaly. It is a congenital cardiac anomaly in which the right ventricle is separated into two chambers, a proximal high-pressure chamber and a distal low-pressure chamber, by anomalous muscles or fibrous tissues in the right ventricular cavity. We report the case of a 6-year-old infant who was admitted for growth retardation. The patient was diagnosed with an isolated DCRV without any other associated congenital anomalies. The patient underwent a successful cardiac surgical procedure of enlargement repair; he was discharged in good clinical condition with a normal cardiac function.